2019
DOI: 10.1002/ijop.12615
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and implementation of the German social–emotional learning programme Papilio in Finland: A pilot study

Abstract: T his study investigated the cross-national adaptation and implementation of Papilio, a German social-emotional learning programme, in Finnish early childhood education and care (ECEC) centres. Papilio is a developmentally focused, scientifically based intervention programme focused on preventing behavioural problems and fostering social-emotional competence in children aged 3-7. The aim of this study was to investigate and evaluate the cross-national adaptation and cross-cultural adaptation and implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Cultural adaptation is a complex process, and despite efforts to plan the learning program and execute it sensitively, unforeseen challenges may still arise. Hence, the target community's perspectives must be considered in cultural adaptation [40]. If a program does not include elements required by the target cultural context, its content and delivery may need to be modified and adapted to better match that culture [41].…”
Section: Discussionmentioning
confidence: 99%
“…Cultural adaptation is a complex process, and despite efforts to plan the learning program and execute it sensitively, unforeseen challenges may still arise. Hence, the target community's perspectives must be considered in cultural adaptation [40]. If a program does not include elements required by the target cultural context, its content and delivery may need to be modified and adapted to better match that culture [41].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the prosocial behaviors of children in Papilio classes significantly improved, while their problematic behaviors (e.g., hyperactivity, inattentiveness symptoms, and emotional, conduct, and peer relationship problems) were reduced compared to control-group children (see Scheithauer et al, 2007). Papilio was piloted and culturally adapted to Finnish ECEC; ECEC personnel's experiences implementing the program and the resulting cultural adaptations were studied (Koivula et al, 2020). The results suggest that Finnish ECEC educators considered the program to have high fidelity and social validity.…”
Section: Previous Research On Provaka and Papiliomentioning
confidence: 96%
“…The Papilio program is a universal, evidence-based intervention developed in Germany to support the development of children's social-emotional competencies and peer relationships while preventing behavioral problems among four-to-seven-year-old children (Mayer et al, 2016). Both of the interventions studied in the current research, ProVaka and Papilio, had been piloted at a Finnish ECEC and reported to be feasible and socially valid in prior studies (Heiskanen et al, 2024;Karhu et al, 2021;Koivula et al, 2020). However, no previous efficacy studies had been conducted on Positive Behavior Interventions and Support in the ECEC of Finland or Nordic countries or on Papilio outside Germany.…”
Section: Introductionmentioning
confidence: 95%
“…Another shortcoming regards the restriction to one context (i.e., Germany), which limits the external validity of the present evaluation. In order to further develop a universal program that can be generalized to different contexts, the cross-national adaptation and implementation of the program has been tested in Finnish kindergartens (Koivula et al, 2020), and scholars from Finland are currently running a trial using this culturally adapted version. The role and involvement of center administrators in the program should be the subject of further study.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%